The Role of Village Apparatus in Village Financial Management Accountability in Wawoangi Village District of South Buton - Pardana, Deki; Daholu, Ahmad (International Journal of Management Progress, 2023)
This study aims to describe the role of village officials in village financial management accountability in Wawoangi Village, Sampolawa District, South Buton Regency. Data collection techniques used in this study were observation, interviews and documentation. While the data analysis technique in this research is descriptive qualitative analysis. Based on the description of the research results and discussion of the war of village officials in the accountability of village financial management in Wawoangi Village, Sampolawa District, South Buton Regency according to the research objectives, it can be concluded that village officials in Wawoangi Village have played a role in village financial management accountability by carrying out their duties starting from from the planning, implementation, administration, reporting, accountability processes carried out according to the responsibilities of each village apparatus in Wawoangi Village and have carried out accountability with the Realization Report of the Implementation of the Wawoangi Village APBDes, although in carrying out their duties there are still village officials in Wawoangi Village who need assistance experts from Sampolawa Subdistrict and assistance from the Wawoangi Village Secretary such as making building designs and RAB (budget plans) which should be made by the Head of Development and also in making Financial Reports carried out only by the village secretary.